Emissão de CO2 do solo em áreas de floresta plantada no Cerrado do Mato Grosso do Sul - Vicentini, Maria Elisa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The increase in CO2 concentration in the Earth's atmosphere was the main cause of global warming, accounting for about 60% of total greenhouse gas emissions. The objective of this work was to characterize the temporal patterns of CO2 emission, temperature, humidity and soil O2 capture, as well as their relationships in areas of Eucalyptus, Pinus and Ciliary forest reforested in a dystrophic Red Latosol in the Biome Cerrado, in the region of the municipality of Selvíria - MS. The study was conducted in three reforested areas located in the municipality of Selvíria-MS. Experimental areas consisted of forests planted with eucalyptus (EU), riparian forest (MA), pinus (PI). The CO2 emission from the soil was recorded using the LI-COR system (LI-8100) and the determination of soil O2 a uptake by means of the UV Flux 25% system. The results of CO2 emission, temperature, humidity and O2 capture were evaluated by means of repeated measures in time, by means of mixed models and descriptive statistics. Tukey's test was performed at a 5% probability level. The ratio of emitted CO2 to O2 consumed (RQ) was calculated. The mean CO2 emission of the soil in the studied areas EU, MA, PI, was 5.61; 5.53 and 4.06. μmol m-2 s-1 respectively. EO2 did not differ statistically in the three areas studied. MA had the highest soil moisture value. Most of the RQ values were <1. The total CO2 emissions recorded in 193 days of evaluation were 11.26 Mg ha-1 for EU 10.99 Mg ha-1, MA and 7,97 Mg ha-1 PI, which differed significantly (p <0, 05). Rainfall and soil moisture influenced the variations of soil CO2 emissions. Pinus forest soils emit less CO2.

O aumento da concentração de CO2 na atmosfera terrestre foi a principal causa do aquecimento global, representando cerca de 60% das emissões totais de gases do efeito estufa. Neste trabalho objetivou-se caracterizar os padrões temporais de emissão de CO2, temperatura, umidade e captura de O2 do solo, bem como, suas relações em áreas de florestas plantadas de Eucalipto, Pinus e Mata ciliar reflorestada em um Latossolo Vermelho distrófico, no Bioma Cerrado, na região do município de Selvíria – MS. O estudo foi conduzido em três áreas reflorestadas localizadas no município de Selvíria–MS. As áreas experimentais consistiam em florestas plantadas com eucalipto (EU), mata ciliar (MA), pinus (PI). A emissão de CO2 do solo foi registrada por meio do sistema LI-COR (LI-8100) e a determinação da absorção de O2 do solo por meio do sistema UV Flux 25%. Os resultados da emissão de CO2, temperatura, umidade e captura de O2, foram avaliados por meio de medidas repetidas no tempo, por meio de modelos mistos e estatística descritiva. Realizou-se comparação de médias pelo teste de Tukey ao nível 5% de probabilidade. Calculou-se a razão entre o CO2 emitido e O2 consumido (RQ). As médias de emissão de CO2 do solo nas áreas estudadas EU, MA, PI, foram de 5,61; 5,53 e de 4,06 μmol m-2 s-1 respectivamente. O EO2 não se diferenciou estatisticamente nas três áreas estudadas. A MA teve o maior valor de umidade do solo. A maior parte dos valores de RQ foram <1. A emissão total de CO2, contabilizados em 193 dias de avaliação foram de 11,26 Mg ha-1 para EU 10,99 Mg ha-1, MA e 7,97 Mg ha-1 PI que se diferiu significativamente (p < 0,05). As precipitações e a umidade do solo influenciaram nas variações das emissões de CO2 do solo. Solos de florestas de Pinus emitem menos CO2.
Soil CO2 emission in forest planted areas of sanava in Mato Grosso do Sul
Keywords: Quociente respiratório; Eucalipto; Pinus; Mata ciliar; Respiratory quotient; Eucalyptus; Pinus; Forest ciliary